The Contribution of Religiosity to Ideology: Empirical Evidences From Five Continents. (December 2018) - Caprara, Gian Vittorio; Vecchione, Michele; Schwartz, Shalom H.; Schoen, Harald; Bain, Paul G.; Silvester, Jo; Cieciuch, Jan; Pavlopoulos, Vassilis; Bianchi, Gabriel; Kirmanoglu, Hasan; Baslevent, Cem; Mamali, Catalin; et al.
The current study examines the extent to which religiosity account for ideological orientations in 16 countries from five continents (Australia, Brazil, Chile, Germany, Greece, Finland, Israel, Italy, Japan, Poland, Slovakia, Spain, Turkey, Ukraine, the United Kingdom, and the United States). Results showed that religiosity was consistently related to right and conservative ideologies in all countries, except Australia. This relation held across different religions, and did not vary across participant's demographic conditions (i.e., gender, age, income, and education). After controlling for basic personal values, the contribution of religiosity on ideology was still significant. However, the effect was substantial only in countries where religion has played a prominent role in the public sphere, such as Spain, Poland, Greece, Italy, Slovakia, and Turkey. In the other countries, the unique contribution of religiosity was marginal or small.